The Regulation Reform of Intellectual Property Following the Advancement of Artificial Intelligence: Guidance and Reevaluation - Astawa, I Gede Putu Harry Gelary; Kurniawan, I Gede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study seeks to examine the impact of ArtificialIntelligence (AI) development on contemporaryintellectual property concepts and regulations, and topropose necessary reforms to address legal challenges insafeguarding works generated by AI. This study employsnormative legal research methodologies, utilizing bothlegislative and conceptual approaches to examine andrevise intellectual property regulations in relation to theadvancement of Artificial Intelligence (AI) technology,through literature reviews and qualitative analysisemploying deductive-inductive reasoning. The study'sfindings indicate that the advancement of ArtificialIntelligence (AI) capable of generating original works haspresented considerable difficulties to the currentunderstanding and governance of intellectual property.Existing legislation, such as the Copyright and Patent Lawin Indonesia, do not recognize AI as a creator or inventor,resulting in legal ambiguities and discussions around theownership rights of AI-generated works. Regulatoryreform is necessary, encompassing the expansion of thedefinitions of creator and inventor, revision of patent laws,modification of regulations pertaining to brands andindustrial designs, establishment of a dedicated institutionfor AI and intellectual property matters, and thedevelopment of suitable implementation and enforcementmechanisms. This reformulation must consideradvancements in international law and need Indonesia'sactive engagement in pertinent global forums.